How Consumers' Skepticism is Derived from Deceptive Advertisements - Shaista Kamal Khan; Hina Fatima; Syed Waqas Hussain (Institute of Business Management, 2020)
This paper aims to explore how consumer behavior is derived by deceptive advertising and their effect that is consumers' skepticism. The advertisement has a significant influence on every single person's life and shapes the consumer's perception. In this study, phenomenological interviews were conducted with three mature females and three males consumers by asking predetermined open-ended questions. The questions had been made to determine the thoughts and feeling about the unlawful, untrue, and mendacious advertisements. The current research shows these symbolic metaphors and highlights the essential meanings that each informant ascribed her consumer encounters. All relevant themes are identified after conducting interviews from participants through data analysis and are further discussed in the results and findings. All findings are interlinked also supported and consistent with earlier studies that are related in this context. The qualitative study ends with some recommendations to companies that think about their consumers and also follow ethical advertising practices.